ANALISIS KAPASITAS DAN KEKUATAN KONSTRUKSI BLADDER TANK PADA SIRKULASI AIR PANAS SISTEM ORC SOLAR KOLEKTOR R-134a - Novianto, Irsan; Gaos, Yogi Sirodz; Alkindi, Hablinur (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
This study focused on component in the Organic Rankine Cycle (ORC), Bladder Tank. The calculation method is based on the calculation stage of plate thickness to withstand the pressure caused by the circulation of the ORC system. The material used is SA 106 with 12mm thickness, Shell length 600mm, 270mm inner diameter and 95mm Head length. From the calculation results obtained maximum pressure on Shell = 253,8385 psi (17,7 bar g) and pressure at Head equal to = 249,6983 psi (17,2 bar g). Bladder Tank Capacity of 38055622,5 mm³ (38,0556 Liter). From result of Pressure Drop simulation got Head loss equal to = 0,00000066 m.